Clinical grade ACE2 as a universal agent to block SARS‐CoV‐2 variants. Issue 8 (4th July 2022) - Monteil, Vanessa; Eaton, Brett; Postnikova, Elena; Murphy, Michael; Braunsfeld, Benedict; Crozier, Ian; Kricek, Franz; Niederhöfer, Janine; Schwarzböck, Alice; Breid, Helene; Devignot, Stephanie; Klingström, Jonas; et al.
Abstract: The recent emergence of multiple SARS‐CoV‐2 variants has caused considerable concern due to both reduced vaccine efficacy and escape from neutralizing antibody therapeutics. It is, therefore, paramount to develop therapeutic strategies that inhibit all known and future SARS‐CoV‐2 variants. Here, we report that all SARS‐CoV‐2 variants analyzed, including variants of concern (VOC) Alpha, Beta, Gamma, Delta, and Omicron, exhibit enhanced binding affinity to clinical grade and phase 2 tested recombinant human soluble ACE2 (APN01). Importantly, soluble ACE2 neutralized infection of VeroE6 cells and human lung epithelial cells by all current VOC strains with markedly enhanced potency when compared to reference SARS‐CoV‐2 isolates. Effective inhibition of infections with SARS‐CoV‐2 variants was validated and confirmed in two independent laboratories. These data show that SARS‐CoV‐2 variants that have emerged around the world, including current VOC and several variants of interest, can be inhibited by soluble ACE2, providing proof of principle of a pan‐SARS‐CoV‐2 therapeutic. Synopsis: Recombinant human ACE2 is reported as a "universal" therapeutic approach, exhibiting strong potency and efficacy for the inhibition of SARS‐CoV‐2 infection, especially toward current variants of concern. SARS‐CoV‐2 variants bind ACE2 ectodomain with increased affinity/avidity. Recombinant soluble ACE2 (APN01) neutralizes all tested SARS‐CoV‐2 variants. Increased binding affinity correlates with increased therapeutic potency. Abstract : Recombinant human ACE2 is reported as a "universal" therapeutic approach, exhibiting strong potency and efficacy for the inhibition of SARS‐CoV‐2 infection, especially towards current variants of concern.